小鼠脑梗死后脑组织HDAC9的表达及其意义 (Nan Fang Yi Ke Da Xue Xue Bao, 2017)
OBJECTIVE: To investigate the expression and the subcellular localization of HDAC9 in different brain regions of mice after cerebral ischemic injury and explore the association between HDAC9 and ischemic stroke. METHODS: Twenty-one male C57BL/6 mice were randomly divided into sham-operated group (n=9) and operated group (n=12). In the latter group, the mice with Zea-Longa neurological deficit scores of 2 or 3 following middle cerebral artery occlusion (MCAO) were assigned into MCAO group (n=9). Immunofluorescence was performed to investigate the subcellular localization of HDAC9 in the brain tissues on day 3 after MCAO. Western blotting and qRT-PCR were used to analyze the expression of HDAC9 in different regions of the brain. RESULTS: Immunofluorescence showed more intense HDAC9 expressions in the brain tissues around the infarct focus, and in the cells surrounding the infarct, HDAC9 expression was obviously increased in the cytoplasm and reduced in the cell nuclei. Compared with the other brain regions, the ipsilesional cortex with MCAO showed more abundant HDAC9 expressions at both the mRNA and protein levels (P < 0.05). CONCLUSION: HDAC9 may be closely related to cerebral ischemic injury and participate in the pathophysiological process of ischemic stroke.